Development of a Performance Management System Artifact Based on Business Intelligence for SMEs: A Design Science Research Methodology Approach - Seifollahi, Mohammadreza (Université d'Ottawa / University of Ottawa, 2022)
Although interest in Performance Measurement and Management Systems (PMMS) and their application in various organizations has grown substantially, they are mainly developed for larger companies, and practitioners find it challenging to implement these systems in Small and Medium-sized Enterprises (SMEs). SME characteristics such as limited budget, lack of experience and knowledge, and pace of change usually make it difficult for managers to adopt and use traditional PMMS. One of the solutions to the lack of applicability of PMMS in the SME context is provided by integrating traditional PMMS with Business Intelligence (BI) and Business Analytics (BA) tools and technologies. The main goal of this thesis is to design and evaluate a Performance Management System based on Business Intelligence (PMS-BI) artifact that contains frameworks, architectures, tools and guidelines to help SMEs evaluate their current Performance Management System (PMS), select the most suitable PMS-BI system components, and design their own PMS based on BI. This artifact also guides them throughout the year by providing tools to assess their PMS-BI and maintain it. For this thesis, I applied a Design Science Research (DSR) methodology to collect the relevant information needed in the design step, design and develop the artifact, and evaluate it. I used the case study approach in the design's information collection and artifact evaluation phases. The final artifact consists of an executive document that guides the SME managers to design their own PMS-BI and helps them have a perception of its efficiency. In the data collection phase, I systematically reviewed the relevant literature to understand best practices, then interviewed eleven participants from seven SMEs to find out the gaps and requirements regarding PMS in SMEs. These participants are directly responsible for the PMS in their organization. Then by combining this information, I extracted the PMS-BI features. In the creative process of system design, I used these features to develop the artifact. Then, I presented the results to the same participants in the form of an executive summary. Finally, I used a “usability questionnaire” to understand participants' opinions about the artifact and document their feedback. My research fills the gap in the application of DSR in the PMS artifact development. This thesis helps researchers understand the application of DSR in designing and developing PMS artifacts for SMEs. In addition, the final artifact can be used by SMEs to develop and apply their own PMS-BI.
Keywords: Performance Measurements; Performance Management; Design Science Methodology; PMS; PMMS; PMS-BI; Business Intelligence; Business Analytics; BI; BA